Practical applications of human language technology the philippine experience - Roxas, Rachel Edita (Philippine computing journal)
In this paper, I present the practical applications of human language technology researches that we have conducted in the country. These applications include fields such as in history, culture and arts, education, law and business. The discussions show that the development of applications for HLT in the country provides a very rich and diverse platform for further research and study, opening up many emerging areas and fields of study.